Studies on the mechanism of efficient extraction of tea components by aqueous ethanol. (1st March 2016) - Hu, Ci-Jie; Gao, Ying; Liu, Yang; Zheng, Xin-Qiang; Ye, Jian-Hui; Liang, Yue-Rong; Lu, Jian-Liang
Highlights: 50% ethanol could efficiently extract catechins and caffeine from tea. Efficient extraction of the solvent might mainly due to its good swelling effect. High solubility might also be involved in high extraction efficiency of the solvent. A pre-swelling extraction can be regarded as an excellent alternative tech. Abstract: Effect of solvent on the extraction yield and its relevant mechanism have been studied in this paper. Compared with extraction by water, catechins and caffeine could be easily extracted from green tea by aqueous ethanol, but hardly at all by absolute ethanol. Results of the vacuum-assisted extraction, solubility determination of EGCG and caffeine, as well as swelling ratio analysis of the infused leaves, indicated that an excellent leaf-matrix-swelling effect and high solubility of tea components might be the key mechanisms for high extraction efficiency by the aqueous ethanol. These mechanisms were further confirmed by the pre-swelling extraction. This is a first report on the mechanism of efficient extraction by aqueous organic solvent. Application of pre-swelling extraction is also discussed.